Sectoral job effects of trade: An input-output analysis for Germany - Maren Lurweg; Jens Oelgemöller; Andreas Westermeier (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
The current globalisation process is characterized by the emergence of global value chains. That is, production processes are becoming increasingly geographically fragmented. Not only are final goods traded internationally, but in particular, trade in intermediate goods and services has increased significantly over time. In the industrialised countries, the manufacturing sectors were the first that were compelled to face the challenges of globalisation. When services were still considered non-tradable, manufacturing firms had already decided to relocate their production sites to developing or emerging economies, due to lower wage levels abroad and increasing price competition domestically. In this paper, we use input-output analysis to explore the relationship between trade and both job creation and job destruction in the German manufacturing industry in 2005. The results show that being integrated into the world economy is advantageous for the German economy. In 2005, the net exports of the manufacturing industries led to trade-induced job gains of around 2,400,000. This figure is equivalent to 6.2 per cent of total German employment. Furthermore, the job effects of trade were positive for a large majority of countries. The greatest job gains resulted from trade with the United States, the United Kingdom and France. Interestingly, even trade with the new EU Member States is beneficial in terms of job creation.
Keywords: F14; F16; C67; 330; input-output analysis; international trade; employment